2013
DOI: 10.1186/1471-2474-14-66
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of angle-stable versus conventional locked intramedullary nails in distal tibia fractures

Abstract: BackgroundIn the last years intramedullary nailing has become the treatment of choice for most displaced diaphyseal tibia fractures. In contrast intramedullary nailing of distal tibia fractures is accompanied by problems like decreased biomechanical stability. Nevertheless the indications for intramedullary nailing have been extended to include even more distal fractures. The purpose of this study was to compare long-term mechanical characteristics of angle-stable versus conventional locked intramedullary nail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Torsional rotation occurs under intramedullary nailing, because of torsional instability of the nail itself, and of flexibility and play of the locking screws. This instability can be reduced by using angle‐stable locking screws . Studies suggest angle‐stable interlocking to improve healing compared to conventional locking, which is in agreement with our findings regarding the negative influence of torsional loading.…”
Section: Discussionsupporting
confidence: 92%
“…Torsional rotation occurs under intramedullary nailing, because of torsional instability of the nail itself, and of flexibility and play of the locking screws. This instability can be reduced by using angle‐stable locking screws . Studies suggest angle‐stable interlocking to improve healing compared to conventional locking, which is in agreement with our findings regarding the negative influence of torsional loading.…”
Section: Discussionsupporting
confidence: 92%
“…Biomechanical studies have demonstrated the advantages for the angular-stable locked nails with regard to a significantly higher axial and torsional stiffness, significantly less fracture gap movement and a significant reduction of the neutral zone in bending [6][7][8][9]. Biomechanically, two ASLS locking screws provide equal stability to three standard locking screws [10].…”
Section: Introductionmentioning
confidence: 99%
“…Newer implants have multiple, multidirectional points of fixation both proximally and distally to provide angular stability [15]. Here the introduction of the ASLS screws improved the stability of different nail constructs as confirmed by biomechanical studies [35,36]. The improvement in interlocking options has expanded nail indications for more proximal and distal shaft fractures.…”
Section: Discussionmentioning
confidence: 93%